2000
DOI: 10.1002/1096-8652(200009)65:1<14::aid-ajh3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A (GATA)7 motif located in the 5? boundary area of the human ?-globin locus control region exhibits silencer activity in erythroid cells

Abstract: A 40-bp DNA, consisting of seven tandem GATA repeats, is located near the HS5 site in the 5' boundary area of the locus control region (LCR) of human beta-globin gene. This (GATA)(7) motif, named 5a, exhibits silencer activity in erythroid cells. In transfected, recombinant plasmids containing the chloramphenicol acetyltransferase (CAT) reporter gene, 5a repressed the activity of the cis-linked housekeeping phosphoglycerate kinase (pgk) promoter; 5a also repressed the activity of the cis-linked HS2 enhancer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
(74 reference statements)
2
14
0
1
Order By: Relevance
“…The CTCF-independent ε-globin gene-specific attenuating activity associated with the HS5 fragment described here could be a novel enhancer-blocking activity which has strict gene specificity, or it could represent a different class of activity contained within the seven tandem copies of GATA motifs, which were reported to repress ε-globin promoter activity in K562 cells (27). It is also possible that this phenotype may be simply due to extending the distance between the LCR and the ε-globin gene promoter because of insertion of the 2.6-kb DNA fragment (the distance between HS2 and the ε promoter expands from 10 kb to 13 kb after insertion of the ectopic HS5 fragment).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The CTCF-independent ε-globin gene-specific attenuating activity associated with the HS5 fragment described here could be a novel enhancer-blocking activity which has strict gene specificity, or it could represent a different class of activity contained within the seven tandem copies of GATA motifs, which were reported to repress ε-globin promoter activity in K562 cells (27). It is also possible that this phenotype may be simply due to extending the distance between the LCR and the ε-globin gene promoter because of insertion of the 2.6-kb DNA fragment (the distance between HS2 and the ε promoter expands from 10 kb to 13 kb after insertion of the ectopic HS5 fragment).…”
Section: Discussionmentioning
confidence: 92%
“…As noted earlier, there are several cis-DNA elements that have been reported to lie within the 2.6-kbp fragment containing human LCR HS5, any of which could potentially attenuate the expression of cis-linked genes (14,27,36). In previous work (32), we inserted an ectopic ε-globin gene 5Ј to HS5 and observed virtually no expression of this gene, while the resident copy of ε in its normal position within the locus was expressed at normal levels.…”
Section: Vol 23 2003 Human ␤-Globin Hs5 Insulator 8947mentioning
confidence: 86%
See 1 more Smart Citation
“…The ERV-9 transcripts may be the originating point of the exclusively nuclear LCR transcripts that are detected at different erythroid developmental stages, and it has been suggested that these transcripts may play a role in creating and/or maintaining an open chromatin configuration (1,20,31). A silencing element consisting of seven tandem GATA repeats is present in the downstream region of human 5ЈHS5 (33). In addition, the presence of a matrix attachment region (MAR) has been reported in a 3-kb fragment encompassing 5ЈHS5 (25) and two topoisomerase II recognition sites, thought to contain this MAR activity, are present just downstream of the 5ЈHS5 core (42).…”
Section: Discussionmentioning
confidence: 99%
“…Silencers bind repressor protein complexes that interfere with promoter activity, thereby down-regulating gene expression (61). Recent data demonstrate that two direct repeat (DR1) elements located in the proximal ε-globin promoter bind a novel repressor activity in definitive erythroid cells called direct repeat erythroid-definitive protein (DRED) (71).…”
mentioning
confidence: 99%